The Role of Export in Boosting Indonesia’s GDP during Crisis: Macroeconomic Conditions - Francisca Sestri Goestjahjanti; Sahala Benny Pasaribu; Dewiana Novitasari; Istajib Kulla Himmy Azz; Winanti Winanti (ETIKONOMI, 2023)
Research examining the determinants of export activities affecting economic growth during the pandemic is gaining global interest, particularly in Indonesia, which recently reduced its fuel subsidy as a unique case in this field. Hence, this study examines the role of export and macroeconomic conditions, including fuel price, exchange rate, and interest rate, in boosting Indonesia’s GDP during the crisis. We examine this relationship by conducting a structural equation model and path analysis on secondary data from 1995-2022. The result shows that both partially and simultaneously, fuel prices, exchange rates, and interest rates significantly affect exports. On the other hand, an increase in export activity improves Indonesian GDP. Thus, simultaneous control of fuel prices, exchange rate, interest rate, and export value can improve Indonesian GDP growth even during the crisis. Based on this result, this article proposes suggestions to the government for a stable fuel price, exchange rate, interest rate, and government policy to promote future economic growth.JEL Classification: E31, E43, F31, C32, O47How to Cite:Goestjahjanti, F. S., Pasaribu, S. B., Novitasari, D., Himmy’azz, I. K., & Winanti. (2023). The Role of Export in Boosting Indonesia’s GDP During Crisis: Macroeconomic Conditions. Etikonomi, 22(2), 369– 388. https://doi.org/10.15408/etk.v22i2.32381.